Docência de inequações no ensino fundamental da Cidade de Indaiatuba - Melo, José João de (2007)
This study discusses the teaching of Inequalities in the elementary school system of Indaiatuba, a town located in the state of São Paulo. Our main goal was to investigate whether the issue of inequalities was being developed in this segment of education and, if so, the way it is being approached. Based on DUVAL s theory of Semiotic Representation Registers and taking into account the prevailing mathematics teaching practices, including the ones described by FIORENTINI in 1995, as well as other practices that have been currently endorsed by mathematics teachers, we drew up a questionnaire filled out by twenty-seven out of thirty-two mathematics teachers working in ten out of forty-two schools in the town of Indaiatuba; the schools were chosen according to the criterion of representativeness. Besides the answers provided through the questionnaire, we also analyzed textbooks used by the assessed teachers in the topics related to inequalities. In assessing the teacher s answers and the textbooks used by them, we noticed the predominance of the algebraic symbolic register approach in the teaching of the mentioned issue. Few conversions are made in class, most of which are the examples shown in the textbooks, leaving the students no alternative but to imitate the schemes already devised. According to existing cognitive analysis, conversion is the activity that best supports the process of understanding; however, if it is conducted by the teacher or by the textbook s author, it accounts very little for the student s learning. As far as teaching methods are concerned, we found a regular occurrence of two of them: the classical formalist and the technicist perspectives, both of which were present in the teachers answers and in the textbooks they use in the classroom. Signs of practices related to more recent approaches can be found in the teachers speech, but not in the textbooks they use. Taking into account both the role of the textbook in the teacher s performance and the analysis conducted, we came to the conclusion that the methods already mentioned and the use of conversions between registers of semiotic representation are not put into practice in the teaching of inequalities in the elementary schools of the town. The teachers adopt teaching methods rather censured in researches related to Mathematics education and merely emphasize the subject of semiotic representation registers, which are not suitable for the students adequate learning. With this in mind, we strongly advise the teachers of this town to take updating training courses on the mentioned issue, aiming to improve the teaching and the learning of the subject in the schools of Indaiatuba. Studies about other subjects based on different theoretical frameworks are also suggested